Welcome to the Inaugural Issue For Our New Chief Editor - Neale Fong (ACHSM, 2022)
Welcome to the inaugural issue of the College's flagship journal with our new Editor-in-Chief, Dr Mark Avery. On behalf of all members, contributors and readers we wish him and the editorial team all the best. Firstly, I would like to thank all members and all those health professionals across our regions for your dedicated service, commitment and support of the community in the past two years during the COVID-19 Pandemic. In Australia we have also seen natural disasters add to workloads and from time to time it really is important to take a moment to acknowledge the fantastic job being done managing through these crises. Thank you. We now have some wonderful analysis from the vast number of College members who have completed the self-assessment against the ACHSM Master Health Service Competency Framework. This report was generated in October last year with 864 overall completions, 732 of those from Australia. Thanks to The Screening Lab who provide the platform for this self-assessment survey and have generated this report from your feedback.....